Exploring Students' Perspectives on the Effectiveness of Peer Assessment: A Qualitative Study - Nabila Chairunnisa; Sukarno (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Peer assessment has been widely implemented as an alternative assessment strategy to promote active learning and student engagement. However, its effectiveness remains debated, particularly from the students’ perspectives. This study aims to explore students’ perceptions of the effectiveness of peer assessment using a qualitative approach. The participants consisted of graduate students who had experienced peer assessment in academic settings. Data were collected through open-ended questionnaires and analyzed using thematic analysis, including coding, categorizing, and interpreting emerging themes. The findings revealed that peer assessment provides several benefits, such as enhancing critical thinking, promoting collaborative learning, and offering diverse perspectives for improving students’ work. However, challenges were also identified, including issues of trust, subjectivity, lack of expertise, and concerns about fairness in evaluation. The study highlights that the effectiveness of peer assessment is strongly influenced by students’ confidence in their peers’ abilities and the clarity of assessment guidelines. This research contributes to the existing literature by providing in-depth qualitative insights into students’ experiences, addressing the gap in understanding the subjective dimensions of peer assessment. It is recommended that educators implement structured guidelines and provide training to optimize the effectiveness of peer assessment.